PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB UNTUK UMKM ECOPRINT - Muhamad Brilliant; Iis ariska nurhasanah (DIBINOM : Digital Business, Economic Jurnal, 2026)
This study aims to develop a web-based sales information system for Yasmin Wiwid Label, an ecoprint-based small and medium enterprise, to support product promotion, online ordering, and sales reporting. The system was developed using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The website provides a product catalog page to display ecoprint products with images, descriptions, and prices, a checkout page to simplify the ordering process, and a sales report dashboard to present revenue and transaction data. Bootstrap 5 was used to create a responsive and clean interface across devices. System functionality was evaluated using black-box testing, and the results showed that all main features worked as expected. The developed system is expected to improve sales management efficiency, support digital promotion, and help the business monitor sales performance more effectively.